2022
DOI: 10.3390/catal12010082
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Production of Fumaric Acid with Immobilised Rhizopus oryzae: The Role of pH and Urea Addition

Abstract: Fumaric acid is widely used in the food and beverage, pharmaceutical and polyester resin industries. Rhizopus oryzae is the most successful microorganism at excreting fumaric acid compared to all known natural and genetically modified organisms. It has previously been discovered that careful control of the glucose feed rate can eliminate the by-product formation of ethanol. Two key parameters affecting fumaric acid excretion were identified, namely the medium pH and the urea feed rate. A continuous fermentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 30 publications
(46 reference statements)
0
34
1
Order By: Relevance
“…It is also critical to highlight that a variation in the amount of H + would result in differences in the amounts of alkali required to control the pH. This is because the acids present may either be as fully dissociated, aqueous undissociated, or solid undissociated acid forms [13]. The stoichiometry of organic acid production and accompanying H + production as a function of pH at standard ambient temperature was previously presented by Taymaz et al [33].…”
Section: Effect Of Caco 3 Additionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is also critical to highlight that a variation in the amount of H + would result in differences in the amounts of alkali required to control the pH. This is because the acids present may either be as fully dissociated, aqueous undissociated, or solid undissociated acid forms [13]. The stoichiometry of organic acid production and accompanying H + production as a function of pH at standard ambient temperature was previously presented by Taymaz et al [33].…”
Section: Effect Of Caco 3 Additionmentioning
confidence: 99%
“…The study found an optimum region for FA production at pH 4, a urea feed rate of 0.625 mg L −1 h −1 , and a glucose feed rate of 0.329 g L −1 h −1 . Moreover, pH 6 was found to be the least favourable condition with regard to FA production [13]. This section of the research study was therefore considered additive, comparing the previously unstudied pH 7 condition to the other three (4, 5, and 6) [13], with a special focus on investigating the conditions that result in MA production.…”
Section: Effect Of Calcium Ionsmentioning
confidence: 99%
See 3 more Smart Citations